UPAYA PEMERINTAH DALAM PEMBERDAYAAN MASYARAKAT ISLAM BERBASIS DESA WISATA GUNA MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DESA AGUSEN KECAMATAN BLANGKEJEREN KABUPATEN GAYO LUES-ACEH - Gayo, Sukri; Nasor, M.; Yanti, Fitri (Universitas Islam Negeri Raden Intan Lampung, 2020)
In an effort to face various challenges and developments, the enactment of Law no. 23 of 2014, in article 221 paragraph 1 that, in the Dutch colonial era Agusen village was a village for the disposal of people affected by leprosy, this village was also a village left behind and far from the hustle / city center, low levels of education, and low economic growth, known as cannabis-producing villages. This study aims to reveal about: (1) Blangkejeren District government efforts in empowering rural tourism-based Islamic communities, their empowerment processes and changes after the process, in order to improve the economy of Agusen village communities, the Type of research used is Field research with a qualitative descriptive approach. Data sourced from primary data and secondary data, with data collection techniques interview, observation, and documentation, as well as data analysis by collecting data, data education, data presentation, and conclusions. The results of research conducted by the Blangkejeren District Government are approaching, the program used to be the village of cannabis now a tourist village, coffee commodity farmers, English language courses, and increasing the entrepreneurial spirit of the community. In the process of empowering the Agusen village-based village tourism community through awareness, planning the Agusen village tourism village program, training and skills development, rural tourism development, coffee farmers commodity, English courses. changes after the process of empowering the village-based tourist community is the emergence of new businesses for the Agusen village community, such as food stalls, coffee shops and also income from admission, parking, and rental of equipment for rafting which is supporting the improvement of the community's economy.